A Predictive Load Balancing Service for Cloud-Replicated Databases - Marinho, Carlos S. S.; Coutinho, Emanuel F.; Costa Filho, José S.; Moreira, Leonardo O.; Sousa, Flávio R. C.; Machado, Javam C. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2017: Anais do XXXII Simpósio Brasileiro de Bancos de Dados, 2017)
Cloud computing emerges as an alternative to promote quality of service for data-driven applications. Database Management Systems must be available to support the deployment of cloud applications resorting to databases. Many solutions use database replication as a strategy to increase availability and decentralize the workload of database transactions between replicas. By the distribution of database transactions between replicas, load balancing techniques improve the computational resources utilization. However, several solutions use the current state of the database service in making decisions for the distribution of transactions. This paper proposes a predictive load balancing service for replicated cloud databases.